2010
DOI: 10.1016/j.ijsu.2009.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of risk factors of incidental parathyroidectomy during thyroid surgery: A prospective study

Abstract: Reoperation for recurrent goitre and concomitant central neck dissection for cancer thyroid may increase the risk of incidental parathyroidectomy. Incidental parathyroidectomy is not associated with symptomatic postoperative hypocalcemia. Most of removed parathyroid glands were intrathyroid, so incidental parathyroidectomy may be unavoidable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
47
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 17 publications
5
47
2
3
Order By: Relevance
“…Sasson et al (16) reported that there was no correlation between hypocalcemia and incidental parathyroidectomy; however, in the current trial, development of hypocalcemia was found to be significant in these patients (P > 0.05). Although the symptoms of hypocalcemia are transient, persistent hypocalcemia has been reported in several series at a rate of 2.1% (17). No persistent hypocalcemia was observed in our series.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Sasson et al (16) reported that there was no correlation between hypocalcemia and incidental parathyroidectomy; however, in the current trial, development of hypocalcemia was found to be significant in these patients (P > 0.05). Although the symptoms of hypocalcemia are transient, persistent hypocalcemia has been reported in several series at a rate of 2.1% (17). No persistent hypocalcemia was observed in our series.…”
Section: Discussioncontrasting
confidence: 48%
“…Attempts to maintain relatively large oncological surgical margins in malignant cases, along with the extra dimensions of the thyroid, are designated as possible causes. Furthermore, another risk factor is the modified radical cervical lymph node dissection performed in thyroid malignancies (16)(17)(18). In a trial performed by Khairy and Al-Saif (19), neither the central nor the modified radical cervical dissections were reported to pose a risk in terms of incidental parathyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Literatürde insidental paratiroidektomi ile hipokalsemi arasındaki ilişki halen tartışmalıdır. İnsidental paratiroidektominin postoperatif hipokalsemi üzerine etkisi olmadığını bildiren çalışmalar olmakla birlikte (24)(25)(26)(27), birçok çalışmada bir veya daha fazla insidental paratiroidektomi yapılan hastalarda geçici hipokalsemi oranı daha yüksek bulunmuştur (8,23,(28)(29)(30). Dört çalışmadan elde edilen 1482 hasta ile yapılan metaanalizde insidental paratiroidektomi yapılan hastalarda geçici hipokalsemi insidansının daha yüksek olduğu saptandı (5).…”
Section: Discussionunclassified
“…Literatürdeki oranlar ise %5-29 arasında değişmektedir (6,8,(23)(24)(25)(26)(27)(28)(29)(30). Yapılan çok değiş-kenli analizlerde insidental paratiroidektomi için total tiroidektomi (28), Graves hastalığı (28), nüks guatr (27), tiroidektomiye ek olarak santral diseksiyon uygulanması (27,29) bağımsız risk faktörleri olarak belirlenmiştir. İnsidental paratiroidektomi yapı-lan paratiroidlerin %50-75'inin intrakapsüler ve intratiroidal lokalizasyonda olduğu bildirilmiştir (25)(26)(27).…”
Section: Discussionunclassified
See 1 more Smart Citation